O lugar da gramática nas diferentes abordagens ao ensino de inglês - Monteiro, Dirce Charara [UNESP] (2014)
Considering the fundamental importance of grammar in any modern language teaching proposal, the aim of this paper is to discuss how the different approaches to the teaching of English as a foreign language (EFL) have considered the role of grammar and the consequences to its teaching.